2012
DOI: 10.1177/1744987112437158
|View full text |Cite
|
Sign up to set email alerts
|

The Arabic version of the Parental Stressor Scale: psychometric properties and Jordanian parents’ stress during child admission to PICU

Abstract: This paper presents an exploration of the validity and reliability of the translated Arabic version of the original English version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…For the PICU population, the main stressors identified by the families were similar to those found in the NICU population. These included the alteration of parenting, 8,12,17,18,20,47 the appearance and behavior of the child, 1,12,[16][17][18]20 the care environment, 1,[16][17][18]20 and communication with the health care staff. 17 These stressors are linked to the PSS: PICU.…”
Section: Pediatric Carementioning
confidence: 99%
See 4 more Smart Citations
“…For the PICU population, the main stressors identified by the families were similar to those found in the NICU population. These included the alteration of parenting, 8,12,17,18,20,47 the appearance and behavior of the child, 1,12,[16][17][18]20 the care environment, 1,[16][17][18]20 and communication with the health care staff. 17 These stressors are linked to the PSS: PICU.…”
Section: Pediatric Carementioning
confidence: 99%
“…The interventions that have been suggested to help family members cope with these stressors aim to foster parental involvement. 12,16,18,20 For example, Lisanti et al 12 suggested encouraging mothers to become actively involved in their child's care by teaching them to carry out simple procedures. The interventions also focused on the development of a visiting schedule for parents to enable them to be present in the ICU at appropriate times and rest at other times.…”
Section: Pediatric Carementioning
confidence: 99%
See 3 more Smart Citations